Anti-inflammation and anti-platelet aggregation activities of the ethanolic extract of Graptophyllum pictum leaves in Wistar rats - Yulia Ratnasari; Susanti Susanti; Binar Asrining Dhiani (Pharmaciana, 2020)
Graptophyllum pictum is a well-known folk medicine in Indonesia. The red leaves are widely used for their anti-inflammatory properties to relieve hemorrhoids. However, little is known about to what extent these properties can affect platelet aggregation. This study was aimed to determine the anti-inflammation and anti-platelet aggregation activities of the ethanolic extract of Graptophyllum pictum (EEGP). Apart from the ear and hind-paw edema assay, anti-platelet aggregation and bleeding time assay were also performed on male Wistar rats. The test animals were grouped into six groups: three treatment groups termed EEGP100, EEGP600, and EEGP3000 (received 100, 600, and 3000 mg/kg BW of EEGP, respectively), one control-solvent group (1% CMC-Na), and two positive control groups (aspirin and Na-diclofenac). Based on the percentage of edema inhibition, absorbance change, and bleeding time, EEGP600 and EEGP3000 produced a comparable percentage of edema inhibition to that of Na-diclofenac, which was not found in EEGP100. Also, EEGP600 and EEGP3000, but not EEGP100, inhibited platelet aggregation as effective as aspirin (positive control). In conclusion, if administered at 600 and 3000 mg/kg BW, the ethanolic extract of Graptophyllum pictum can function as an anti-inflammatory agent that inhibits platelet aggregation.Â